Application Of Global Strain Extensometer (Glostrext) Method For Instrumented Bored Piles In Malaysia - Abdul Aziz Hanifah (Deep Foundations Institute, 2006)
A novel instrumentation and analysis technique, called GLOSTREXT method has recently been introduced for bored pile load tests in Malaysia. This technique provides an innovative and improved alternative for conventional bored pile instrumentation methods commonly practiced for the past few decades. Results for five case histories involving full scale static load tests for high capacity bored piles with both new and conventional instrumentation details placed in within the same instrumented piles are presented to demonstrate the advantages of this novel technique. Results show good agreement between the new and conventional instrumentation.